Multivariate methods in epidemiology - Holford, Theodore R. (New York ; Oxford : Oxford University Press, 2002)
This text describes the statistical tools that are currently used to analyse epidemiologic data on the association between possible risk factors and the actual risk of disease.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Epidemiology -- Statistical methods; Multivariate analysis